The challenge of marketing independent inventions: an international prerogative. (1st January 2001) - Nancarrow, Clive; Attlee, Celia; Wright, Len Tiu
This paper examines the peculiar entrepreneurial hiatus surrounding inventions from independent inventors in the UK which, it is argued, limits its international competitiveness. Evidence that many other countries stimulate and exploit independent inventors to a greater degree is assessed, and it is concluded that the UK fails to capitalise on the innovations from this pool of talent. A programme of exploratory research is carried out to identify the reasons for this and identify lessons that have relevance to invention and innovation internationally. The research programme consists of a review of the literature and past research, a survey of the global Internet as well as qualitative research consisting of personal and telephone interviews and written correspondence. The latter examined, in particular, the marketing communication process between inventors and potential adopter marketing organisations. The sample comprised "successful" independent inventors (some of international and national repute) who marketed nationally and or internationally, potential adopter manufacturing and marketing organisations, and a number of organisations with a role of facilitating the adoption process. The findings from the various sources seemed largely to complement each other and indicated a major need for all parties to re-consider their strategies. The paper puts forward detailed recommendations that, it is argued, may have international relevance.